FORMULATION OF LOCAL DEVELOPMENT POLICY FOR YOUTH IN SOUTH TANGERANG CITY - Evi Satispi; Muhammad Taslim (Kolaborasi : Jurnal Administrasi Publik, 2019)
Social problems in youth become a matter that is always considered and reviewed by the government for the development of the personality of these young people. This study aims to analyze the policy formulation of Regional Regulation No. 1 of 2019 concerning Youth Development in South Tangerang. Youth Development Policy Formulation departs from youth issues including unemployment, youth behavior that is at risk of crime, thuggery, and drug abuse, there is no legal umbrella governing youth development in the city of southern Tangerang and youth infrastructure. The method used is descriptive with a qualitative approach. This research uses the theory of the Riant Nugroho formulation stage, while the stages start from policy issues, forming a formulation team, pre-policy process, public process 1, formulation of draft 1, public process 2, formulation of draft 2, special focus, final draft and determination of policy . In the policy formulation stages Riant Nugroho prioritizes the stages in formulating a policy regulation or law. The results showed that the stages in formulating youth development policy formulation by the south tangerang city government had been implemented well so as to produce a youth development policy in south tangerang. Not only the stages of formulation that are of concern from the internal side, youth also experience obstacles such as cross-regional Cooperation Organizations that have not been synchronized in terms of youth development and empowerment programs as well as inadequate infrastructure facilities that encourage youth development and empowerment.